2017
DOI: 10.1002/2017gb005693
|View full text |Cite
|
Sign up to set email alerts
|

Release of Black Carbon From Thawing Permafrost Estimated by Sequestration Fluxes in the East Siberian Arctic Shelf Recipient

Abstract: Black carbon (BC) plays an important role in carbon burial in marine sediments globally. Yet the sequestration of BC in the Arctic Ocean is poorly understood. Here we assess the concentrations, fluxes, and sources of soot BC (SBC)—the most refractory component of BC—in sediments from the East Siberian Arctic Shelf (ESAS), the World's largest shelf sea system. SBC concentrations in the contemporary shelf sediments range from 0.1 to 2.1 mg g−1 dw, corresponding to 2–12% of total organic carbon. The 210Pb‐derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 104 publications
1
19
0
Order By: Relevance
“…The results of this study indicate that terrestrially sourced CM in the East Siberian Arctic region can be found in sediments hundreds of kilometres offshore. Whilst direct quantification of CM as a fraction of total OC is not possible using Raman spectroscopy, chemical analyses show that SBC could account for 14 % of terrestial OC in distal sediments (Salvadó et al, 2017). Highly Graphitised CM is structurally similar to SBC and the chemothermal treatment used in these studies likely removes low-grade CM, implying that CM concentrations could be similar to, if not higher than, SBC offshore.…”
Section: Implications For Carbon Cycling In the Esasmentioning
confidence: 90%
See 1 more Smart Citation
“…The results of this study indicate that terrestrially sourced CM in the East Siberian Arctic region can be found in sediments hundreds of kilometres offshore. Whilst direct quantification of CM as a fraction of total OC is not possible using Raman spectroscopy, chemical analyses show that SBC could account for 14 % of terrestial OC in distal sediments (Salvadó et al, 2017). Highly Graphitised CM is structurally similar to SBC and the chemothermal treatment used in these studies likely removes low-grade CM, implying that CM concentrations could be similar to, if not higher than, SBC offshore.…”
Section: Implications For Carbon Cycling In the Esasmentioning
confidence: 90%
“…Soot black carbon (SBC) is a complementary portion of the recalcitrant OC load in the ESAS. Salvadó et al (2017) studied SBC using chemical methods (chemothermal oxidation to remove non-SBC, followed by elemental analysis and stable/radiocarbon isotope mass spectrometry), which allowed for quantification of 'SBC' and source apportionment. This method does not directly measure the nature of SBC particles, in contrast to Raman analysis, but allows for quatification rather than investigating relative changes.…”
Section: Comparison With Soot Black Carbonmentioning
confidence: 99%
“…In the outer plume only about 2 % of the total OC was present as POC. It has been suggested that POC in the Lena River freshwater plume is transported in different forms, including large particles, which can sink, and almost neutrally buoyant flocculates of humic substances (Gustafsson and Gschwend, 1997;Gustafsson et al, 2000;Sánchez-García et al, 2011). The POC, which is as- sociated with larger particles (> 0.7 µm), will settle close to land, whereas the humic substance flocculates will travel further out .…”
Section: Discussionmentioning
confidence: 99%
“…High-purity Suprapure ® acids were used throughout sample treatment and analysis. Organic carbon analyses were carried out at Stockholm University (for analytical details; see Alling et al, 2010;Sánchez-García et al, 2011). For element analysis, the water samples (colloidal: 1 kDa to 0.22 µm; truly dissolved: < 1 kDa) were diluted (2-200 fold) with 10 % HNO 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation